Expression of the receptor for advanced glycation end products in acquired reactive perforating collagenosis - Sungu, Nuran; Akoglu, Gulsen; Aktas, Akin; Karaismailoglu, Eda (Scientific Scholar, 2017)
Acquired reactive perforating collagenosis (ARPC) is a rare skin disorder characterized by transepidermal elimination of dermal collagen. There is little data regarding the pathogenesis of ARPC. The receptor for advanced glycation end products (RAGE) is a multiligand transmembrane receptor that plays an important role in inflammatory responses and may be involved in the pathogenesis of ARPC.To explore the expression of RAGE in ARPC.Paraffin-embedded punch biopsy specimens of 41 patients with ARPC and of 11 healthy controls with normal skin were obtained from the Department Of Pathology. Clinical data of all patients were reviewed from the medical files. All specimens were stained immunohistochemically with antibody to RAGE (Anti-RAGE). The intensity of RAGE expression was assessed semi-quantitatively on epidermal cells, microvascular endothelium, dermal fibroblasts and inflammatory cells and graded as 0 (no staining), 1 (weak), 2 (moderate) and 3 (strong). The patients were divided into diabetic and nondiabetic groups for analysis.RAGE expression in microvascular endothelium, inflammatory cells and fibroblasts of patients with ARPC was more intense than normal tissues of healthy participants (P values are 0.005, 0.017 and P > 0.05).Our method of assessment of RAGE expression was semi-quantitative.We observed an overexpression of RAGE in lesional samples of patients with ARPC which was independent of the presence of diabetes.
Keywords: Adult; Male; Receptor for Advanced Glycation End Products; Collagen Diseases; Gene Expression; Middle Aged; Antigens, Neoplasm; Humans; Female; Mitogen-Activated Protein Kinases; Aged; 3. Good health